A comparison of the efficacy of reducing the signs of ageing in the neck skin after polynucleotides injections in regimens with different dosing intervals – a case study (Journal of Face Aesthetics, 2023)
Introduction. The article presents the case of a 59-year‑old female patient with signs of the neck skin ageing who underwent treatment based on fish‑derived polinucleotides injections using two different regimens. Aim. To compare efficacy of the regimens A and B.Material and methods. Intradermal injections were administered in two schemes (A and B), considering the following intervals: four treatments 2 weeks apart for scheme A (left half of the neck) and four treatments 4 weeks apart for scheme B (right half of the neck). Analysis of skin parameters was performed using the set of probes Cutometer Dual MPA 580 probe Courage+Khazaka electronic GmbH (cutometer, corneometer, mexameter, evaporimeter). Measurements were always taken at the same points on the both sides of the neck.Results. The patient was treated without persistent side effects. No improvement in cutometer parameters has been observed after treatment with Scheme A on both neck and mandible site. In contrast, the use of Scheme B resulted in increases in parameters R2 (the only significant effect). The application of both regimens resulted in more consistent melanin results in the neck and mandibular regions. In addition, regimen A was more effective in reducing skin redness at both sites, while regimen B was more effective in improving skin condition and resulted in a greater increase in skin hydration in the mandibular site. Conclusions. The skin benefited more from Scheme B. Treatment with polynucleotides extends the anti‑ageing therapy options but is characterised by a mild effect. In mature patients it should be used rather as a form of prevention than as a method of reversing the effects of ageing.
Keywords: polynucleotides; neck skin; biorevitalization; anti‑ageing therapies; cutometer